Corazón - De Amicis, Edmondo, 1846-1908 (Akal bolsillo ;, 2014)
This italian novel, written in the mid 19th century and dealing with the fictional diary of Enrico Bottini, a 10-year old boy, during his third year at a school in Turin, Italy. He records his thoughts and feelings in fifty episodes. Every story revolves around a different moral value, the most prominent of which are helping those in need, having great love and respect for family and friends, and patriotism. One of the most worldwide famous works, that in addition to being tender, gives us great lessons of life.